A Highly Elastic and Reversibly Stretchable All‐Polymer Supercapacitor. Issue 44 (18th September 2019) - Wang, Yukun; Chen, Feng; Liu, Zhuoxin; Tang, Zijie; Yang, Qi; Zhao, Yan; Du, Shanyi; Chen, Qiang; Zhi, Chunyi
Abstract: Multiple stretchability has never been demonstrated as supercapacitors because the hydrogel used cannot fully recover after being heavily deformed. Now, a highly reversibly stretchable all‐polymer supercapacitor was fabricated using a developed double network hydrogel (DN hydrogel) as electrolyte and pure polypyrrole (PPy) as electrode. The DN hydrogel provides excellent mechanical properties, which can be stretched up to 500 % many times and then restore almost 100 % of the original length. To fabricate the fully recoverable stretchable supercapacitor, we annealed a free‐standing pure conducting polymer film as electrode so that the electrodes induced retardance is minimized. The as‐fabricated DN hydrogel/pure conducting polymer supercapacitors can be perfectly recovered from 100 % strain with almost no residual deformation left and the electrochemical performance can be maintained even after 1000 stretches (but not bending). Abstract : Elastic supercaps : An agar/hydrophobically associated polyacrylamide (HPAAm) double network (DN) hydrogel and pure polypyrrole (PPy) film based all‐polymer supercapacitor was fabricated. It is highly elastic and reversibly stretchable. This supercapacitor can be stretched and recovered for 1000 times with no obvious performance degradation and strain residue, exhibiting excellent elasticity at the device level.